Status of respiratory virus infections in Turkey - Payzın, Sabahattin (The Turkish Journal of Pediatrics, 1963)
Data are presented for the etiological agents and antibodies for respiratory infections in the different communities of Turkey. Q fever and adenovirus infections are common diseases when there is no epidemic of influenza.